ASSESSING FISHERY LEGISLATION FOR GENDER EQUALITY AND EMPOWERMENT IN FISHERY COMMUNITIES IN INDONESIA - Ani Purwanti; Dyah Wijaningsih; Muh. Afif Mahfud; Fajar Ahmad Setiawan (Diponegoro Law Review, 2021)
The research objective was to analyze the problem of fisherwomen empowerment and gender equality based on legal reviews in Indonesia. The research method used is normative legal studies. The results of the study found that there are discriminatory implications in Law Number 7 of 2016 concerning the Protection and Empowerment of Fishermen, Fish Farmers, and Salt Farmers or commonly referred to as the PEF Act (Protection and Empowerment of Fishermen) which is not in line with the empowerment of fisherwomen and is in conflict with gender equality. The findings make it clear that fisherwomen, unlike other economic actors in the fishing industry, are the most overlooked group rooted in socio-cultural prejudice. The PEF Act does not specifically recognize or even mandate any form of affirmative action for fisherwomen to gain equal access to protection and empowerment programs. This causes fisherwomen who have been culturally forcibly placed in households and away from the fishing industry. But instead, the PEF Act dwarfed the position of women as a mere secondary role in fishery households instead of the main breadwinner. Therefore, this study suggests that the government should make a strict amendment to the PEF Act. Namely recognizing gender equality in the role of fisherwomen and followed by reforming gender mainstreaming in the fisheries bureaucracy to accommodate fisherwomen's rights to access community empowerment programs for fishing communities.